2011
DOI: 10.1021/jz200797g
|View full text |Cite
|
Sign up to set email alerts
|

The “Protein Dynamical Transition” Does Not Require the Protein Polypeptide Chain

Abstract: P rotein dynamics is characterized by molecular motions occurring on a very large time-scale ranging from femtoseconds (vibrations) to seconds (long-range molecular diffusion). Within this broad interval, motions occurring in the pico-to nanoseconds time scale are of particular interest and biological relevance since they cover the transition region from "discrete" local excitations of small molecular subunits to slower processes involving cooperative motions of larger parts of the macromolecular assembly.1 Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…The Mean Square Displacements (MSDs) of the hydrogen atoms and the density of states resulted those of a harmonic solid, while in D 2O-hydrated myoglobin (Mb) a dynamical transition to a non-harmonic behavior was present at ~180 K [103][104][105][106], dependent on the hydration level. Therefore, it was suggested that, in the whole temperature range investigated, the trehalose matrix entraps myoglobin in a harmonic well.…”
Section: Atomistic Levelmentioning
confidence: 99%
“…The Mean Square Displacements (MSDs) of the hydrogen atoms and the density of states resulted those of a harmonic solid, while in D 2O-hydrated myoglobin (Mb) a dynamical transition to a non-harmonic behavior was present at ~180 K [103][104][105][106], dependent on the hydration level. Therefore, it was suggested that, in the whole temperature range investigated, the trehalose matrix entraps myoglobin in a harmonic well.…”
Section: Atomistic Levelmentioning
confidence: 99%
“…Experimental studies show that the protein hydration water plays a key role in many aspects of protein behavior, which include the mean square displacement of the protein constituent atoms [2][3][4], the subpicosecond collective vibrations [5][6][7][8], the intraprotein α and β fluctuations [9,10], and the protein enzymatic activity [11]. Thus the study of the protein hydration water is crucial for the understanding of protein dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…What is the physical mechanism responsible for the water driven effect giving rise to the PDT? A clue is obtained from the fact that the same PDT onset temperature of $220 K is observed for chemically and structurally different hydrated peptide systems like native and denaturated proteins, HP (even for poly-G that accounts for the ''pure backbone'' contribution), amyloid fibrils [24] and amino acid mixtures lacking the polypeptide chain [25]. This implies that the ÁG and ÁG Ã values, that set the PDT onset temperature in these systems, are determined by hydration water.…”
mentioning
confidence: 99%